Boosted Productivity in Single‐Tile‐Based DNA Polyhedra Assembly by Simple Cation Replacement. (23rd June 2022) - Zhou, Kaixuan; Mei, Zhichao; Lei, Yunxiang; Guan, Zhen; Mao, Chengde; Li, Yulin
Abstract: Cations such as divalent magnesium ion (Mg 2+ ) play an essential role in DNA self‐assembly. However, the strong electrostatic shielding effect of Mg 2+ would be disadvantageous in some situations that require relatively weak interactions to allow a highly reversible error‐correcting mechanism in the process of assembly. Herein, by substituting the conventional divalent Mg 2+ with monovalent sodium ion (Na + ), we have achieved one‐pot high‐yield assembly of tile‐based DNA polyhedra at micromolar concentration of tiles, at least 10 times higher than the DNA concentrations reported previously. This strategy takes advantage of coexisting counterions and is expected to surmount the major obstacle to potential applications of such DNA nanostructures: large‐scale production. Abstract : A simple yet efficient strategy for avoiding the concentration‐dependent kinetic trap in DNA self‐assembly is proposed. Through substituting monovalent Na + for conventional divalent Mg 2+, we have successfully achieved one‐pot high‐yield assembly of tile‐based DNA polyhedra at micromolar concentration of tiles, at least 10 times higher than the concentration reported previously.